Implementasi Pembelajaran Sosial Emosional Berdasarkan Kerangka CASEL di Sekolah Dasar - Elvianti Amri (LPPI Yayasan Almahmudi bin Dahlan, 2025)
Social Emotional Learning (PSE) plays an important role in character building and student academic success. The CASEL (Collaborative for Academic, Social, and Emotional Learning) model introduces five core competencies that are essential in the social-emotional development of learners. This article aims to analyze the implementation of CASEL framework-based social-emotional learning at the primary school level and review its relevance in improving classroom climate and learning achievement. Using a literature review approach, this article finds that the systematic and contextual implementation of CASEL is able to improve students' empathy, self-management and social relationship skills. Teachers play a central role as facilitators in integrating PSE into daily learning.